Irradiation as a Food Preservation Method in Nigeria: Prospects and Problems - SULEMAN Kamaldeen Olasunkanmi (IJRASET, 2015)
Food irradiation is a food preservation method which involves the process of exposing foodstuffs to a source of energy capable of stripping electrons from individual atoms in the targeted material (ionizing radiation). This method of food preservation can be referred to as a more advanced form of food preservation. Some school of thought criticize the use of irradiation for food preservation because of the negative impressions of the nuclear industry, and this has made irradiation one the most investigated forms of food preservation. Food irradiation has been endorsed by the World Health Organization (WHO), and is currently being used in over 40 countries and approximately 500,000 tons of food items are irradiated yearly all over the world. This work has highlighted some problems associated with the use of food irradiation technology in Nigeria, and has also proffered solutions that can help tackle the said problems. This work has also discussed the process of food irradiation, the recommended sources and the dose range required for effective irradiation of food products.
Keywords: rradiation; Prospects; Problems; Food preservation; Nigeria.